127k views
5 votes
Ax-bx+y=z solve for x

2 Answers

7 votes

Answer:

The solution for x will be:


x=(z-y)/(a-b)

Explanation:

Given the expression


ax-bx+y=z

subtract y from both sides


ax-bx+y-y=z-y

simplify


ax-bx=z-y

Factor ax-bx = x(a-b)


x\left(a-b\right)=z-y

Divide both sides by a-b; a≠b


(x\left(a-b\right))/(a-b)=(z)/(a-b)-(y)/(a-b);\quad \:a\\e \:b

simplify


x=(z-y)/(a-b);\quad \:a\\e \:b

Therefore, the solution for x will be:


x=(z-y)/(a-b)

User Ashanrupasinghe
by
5.1k points
9 votes

Answer:

x = (z - y)/(a - b)

General Formulas and Concepts:

Algebra I

  • Equality Properties
  • Factoring

Explanation:

Step 1: Define

ax - bx + y = z

Step 2: Solve for x

  1. Subtract y on both sides: ax - bx = z - y
  2. Factor GCF: x(a - b) = z - y
  3. Isolate x: x = (z - y)/(a - b)
User Basic Bridge
by
4.7k points